310. Longitudinal Assessment of Point-of-Care LumiraDx Antigen and Antibody Test Performance During Acute SARS-CoV-2 Infection and Recovery. (15th December 2022) - Dalmat, Ronit; Prabhu, Roshni; Bauer, Marie; Ikuma, Matthew H; Hamilton, Daphne; Rechkina, Elena A; Cantera, Jason L; Grant, Benjamin D; Drain, Paul K
Abstract: Background: Rapid COVID-19 tests can offer significant advantages and reduce health disparities. The LumiraDx SARS-CoV-2 platform can perform microfluidic fluorescence assays for the rapid detection of SARS-CoV-2 antigen (Ag) and antibodies (Ab). We evaluated both tests in a longitudinal cohort to evaluate performance during acute SARS-CoV-2 infection and recovery. Methods: We collected nasal samples from 71 unique participants at four clinic visits spanning 0-21 days since symptom onset (DSSO); blood samples were collected from the same participants over six visits spanning 0-87 DSSO. For Ag testing, 232 anterior nasal swabs were assayed by: 1) the LumiraDx Ag test, 2) a laboratory-based electrochemiluminescence immunoassay for N Ag, 3) RT-PCR (Hologic Panther Fusion), and 4) culture (growth in VeroE6AT cells). For Ab testing, 308 serum samples were assayed by: 1) the LumiraDx Ab test and 2) Roche Elecsys Anti-S SARS-CoV-2 total Ab test. Measures of concordance [positive predictive agreement (PPA), negative predictive agreement (NPA), and Cohen's Kappa (Κ)] were estimated for qualitative results of the LumiraDx tests versus corresponding lab reference tests. Confidence intervals were estimated via bootstrapping. Results: LumiraDx Ag results had strong agreement with lab N-Ag results (Κ > 0.80) across all samples. Between 0-5 days, agreement was perfect, except for one sample resulting positive by LumiraDx Ag and negative by lab Ag. Agreement with PCR results was moderate overall (Κ=0.60), though substantial (Κ > 0.6) for both 0-5 DSSO (PPA=0.96/NPA=0.80) and 6-10 DSSO (PPA=0.96/NPA=0.59). Agreement with culture results was moderate overall (Κ=0.46): substantial (Κ=0.6) between 0-5 DSSO (PPA=0.96/NPA=0.60) and fair (Κ=0.29) between 6-10 DSSO (PPA=1.0/NPA=0.32). LumiraDx Ab results showed almost perfect agreement with lab Ab results across all samples (Κ=0.88), with substantial agreement (Κ > 0.7) for samples collected 0-10 DSSO (PPA=0.93/NPA=0.89) and 11-28 DSSO (PPA=0.99/NPA=0.69). Longitudinal agreement of LumiraDx antigen test result and culture positivity, by PCR Ct value. Nasal samples grouped by participant (lines) and agreement of results between LumiraDx antigen test result and culture positivity (proxy for infectiousness). Conclusion: LumiraDx rapid tests perform well compared to more costly and time-consuming lab methods of Ag and Ab detection. The rapid Ag test may be helpful in identifying patients infectious between 0-5 DSSO, given the substantial concordance of the rapid Ag test and culture positivity. Disclosures: Daphne Hamilton, BA, Roche (spouse is employed by Roche): Employee.